SIMULATION OF EQUATION OF MOTION OF THE NEW CONSTRUCTION GIN MACHINE. - Azizov, Shuhrat (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
The article analyzes the moving mechanisms of the new gin design, creates kinematic diagrams of the feed rollers, peg drum, saw cylinder shafts and auger shaft for removing dead fiber. Based on the kinematic diagrams, dynamic models and equations of motion of the feed rollers, peg drum, saw cylinder shafts and auger shaft are created.